Assessment of Fish Consumption Patterns in the Lake Victoria Basin of Uganda - Zech, Halasi Gidongo; Shuwu, Hyuha Theodora; Ekere, William; Elepu, Gabriel; Walakira, John; Molnar, Joseph; Kalumba, Sloans Chimatro; Egna, Hillary (American Journal of Agriculture, 2024)
Purpose: To establish fish consumption patterns and its determinants in the study area. Materials and Methods: The study used random and stratified sampling methods to obtain a sample size of 621 fish consumers from Mayuge and Masaka districts. This study used primary data. Stata and statistical package for social sciences (SPSS) were used in data analysis. Frequencies, mean, percentages, inferential statistics were used to achieve the objectives of this study. Data was presented in tables and graphs. Findings: Respondents mostly ate farmed tilapia (64%), captured tilapia (92%), captured Nile perch (84%). Sun dried silverfish was consumed at a level of 99%. Fish product consumption levels were negligible. Regression analysis established that fish price, education level, household income, location of resident, price of chicken, fish form consumed, fish fat level, production system of fish consumed and variation in fish availability significantly influenced monthly quantities of fish consumed. Implications to Theory, Practice and Policy: The study recommended the need to improve household income, make the community aware of the nutritiousness of fish and its associated advantages and increase fish price competitiveness by improving efficiency in availing fresh fish to selling locations. Improvement was needed in fish management to put to market, highly nutritive and healthy farmed fish. Need to promote processed fish consumption for both captured and farmed fish. Lastly a vigorous drive to increase farmed fish consumption was key.